Executive Functioning as a Predictor of Weight Loss and Physical Activity Outcomes. Issue 10 (25th January 2019) - Butryn, Meghan L; Martinelli, Mary K; Remmert, Jocelyn E; Roberts, Savannah R; Zhang, Fengqing; Forman, Evan M; Manasse, Stephanie M
Abstract: Background: Executive functioning, which is fundamental for carrying out goal-directed behaviors, may be an underappreciated predictor of outcomes in lifestyle modification programs for adults with obesity. Purpose: This study tested the hypotheses that higher levels of baseline executive functioning would predict greater weight loss and physical activity after 6 months of behavioral treatment. Methods: Participants ( N = 320) were recruited from the community and provided with 16 treatment sessions. Executive functioning was measured with the tower task component of the Delis-Kaplan Executive Function System (D-KEFS). At months 0 and 6, weight was measured in the clinic and physical activity was measured with tri-axial accelerometers. Results: Baseline D-KEFS achievement score, rule violations, and completion time significantly predicted weight loss at 6 months. For example, among participants without any rule violations ( n = 162), weight loss averaged 11.0%, while those with rule violations ( n = 158) averaged 8.7% weight loss. Rule violations also significantly predicted physical activity at 6 months. Among participants without any rule violations, physical activity at 6 months averaged 169.8 min/week, versus 127.2 min/week among those with rule violations. Conclusions: Particular aspects of executive functioning may predict the relative ease or difficulty of changing eating and exercise-related behaviors, albeit with small effect sizes. This study is the first to our knowledge to detect a predictive relationship between components of executive functioning and objectively measured physical activity in adult lifestyle modification, and one of the first to predict weight loss in adults using an objective measure of executive functioning. ClinicalTrials.gov registration number: NCT02363010 Abstract : Executive functioning may predict the relative ease or difficulty with which an individual changes eating and exercise-related behaviors.